Geothermal energy use in absorption precooling for Claude hydrogen liquefaction cycle. (13th July 2016) - Kanoglu, Mehmet; Yilmaz, Ceyhun; Abusoglu, Aysegul
Abstract: We propose an integrated system that consists of an ammonia-water absorption refrigeration cycle for the precooling of hydrogen, and the Claude cycle for the liquefaction of hydrogen. Geothermal energy supplies heat to the generator of the absorption system. A liquid geothermal source available at 200 °C at a rate of 100 kg/s is considered. The system is analyzed thermodynamically by the first and second laws using appropriate performance parameters. Under realistic operating conditions 39, 080 kW heat can be supplied by geothermal water in the absorption refrigeration system. Hydrogen gas can be cooled to −26.9 °C at a rate of 29.53 kg/s in the absorption unit. The coefficient of performance (COP) of the ammonia-water refrigeration system is determined to be 0.556 with an exergy efficiency of 67.0%. The COP of the Claude liquefaction system is 0.0120 and its exergy efficiency is 67.3%. For the overall system, the COP and exergy efficiency are 0.162 and 67.9%, respectively. Also, precooling hydrogen gas in an absorption refrigeration cycle powered by geothermal heat decreases the work consumption in the liquefaction process by 25.4%. Highlights: Hydrogen is cooled in an ARC and hydrogen is cooled in a Claude cycle. The integrated system is analyzed thermodynamically by the first and second laws. Hydrogen is cooled to −26.9 °C at a rate of 29.53 kg/s for a geothermal flow of 100 kg/s. The COP and exergy efficiency of the system are 0.016 and 67.9%, respectively. Precooling hydrogen gas in the ARC decreases the work of liquefaction by 25.4%.